Hubungan Intensitas Penggunaan Media Sosial dengan Kesehatan Mental Mahasiswa dalam Pendidikan Agama Islam - Muhammad Zakwan Nawafi; Rendi Putra Dwiyan; Hafidz Ma`ruf Huda (Jurnal Budi Pekerti Agama Islam, 2024)
In the era of advancing information and communication technology, using the internet has become very easy. This is due to the need for access to information, lifestyle, communication, entertainment, and knowledge available on various social media platforms. Social media plays a role in shaping a person's identity, and high social media use among students can impact their mental health. This study aims to determine the relationship between the intensity of social media use and the mental health of PAI students at Ibn Khaldun University, Bogor. The research method used is quantitative with a correlational approach. The subjects in this study were 87 PAI students. The sampling technique was simple random sampling. Data analysis was conducted using the Product Moment Correlation test. The results showed a significant negative relationship between the intensity of social media use and the mental health of PAI students. The correlation coefficient was r = 0.220 with a significance level of p = 0.041 (< 0.05). This means that the higher the students' intensity of social media use, the lower their mental health. Conversely, the lower the intensity of social media use, the better their mental health.